Usulan Penerapan Pemasaran Digital Menggunakan Model PRACE untuk Beras Organik Galunggung Farm - Firda Indriyani; Irfan Ardiansah (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2022)
Digital marketing is very important because of the advancement of industry in the world, making many companies use digital marketing in promotion and sales so that the use of digital media increases. This makes Galunggung Farm want to develop sales by developing new markets by focusing on market development towards B2C (Business to Customer), therefore Galunggung Farm utilizes digital marketing for new situations and strategies. The digital media used for digital marketing is Instagram. This study aims to determine the current state of Galunggung Farm's digital marketing based on the analysis of the PRACE framework (Plan, Reach, Act, Convert, and Engage) and produce goals and KPIs (Key Performance Indicators) of Galunggung Farm's digital marketing based on the results of the initial analysis. The method used is PRACE (Plan, Reach, Act, Convert, and Engage). The results of the analysis show that in the current social media marketing of Galunggung Farm, several things can be improved. Based on this, the company's objectives are stated, namely: 1) Build brand awareness and follower conversion, 2) Initiate brand interaction, 3) Achieve sales conversion, 4) Reach fans and initiate brand engagement, resulting in KPI (Key Performance Indicator) for social media Instagram Galunggung Farm are 1) Reach (Reach and followers), 2) Act (likes and comments), 3) Convert (content saved and conversation rate), 4) Engage (content shared, online reviews, users testimonials, and recommendations).